Effect of an ankle compression garment on fatigue and performance - Sambaher, N.; Aboodarda, S. J.; Silvey, D. B.; Button, D. C.; Behm, D. G. (The Journal of Strength and Conditioning Research, 2016)
The aim of this study was to examine the effects of an ankle compression garment (CG) on muscle performance and physiological variables associated with recovery from fatigue. Fifteen participants took part in a randomized crossover study design with 2 experimental conditions (ankle CG and control). The dependent variables skin temperature, evoked muscle contractile properties, maximal voluntary contraction (MVC) force, electromyography (EMG), drop jump performance (20, 35, and 50 cm box heights), continuous drop jump (30 cm), time to fatigue (TTF), and blood lactate concentration were measured pre- and post-warm-up and postfatigue. Compared with control condition, ankle CG condition had significantly reduced half-relaxation times (p = 0.043) and higher skin temperatures at post-warm-up and post-fatigue protocol (p < 0.001, Delta 3.2 and Delta 4%, respectively). Participants also exhibited significantly lower ground reaction forces (GRFs) for 50-cm drop jumps (p = 0.044, Delta 9.9%) with ankle CG at post-warm-up. There were no significant differences between conditions for muscle contractile properties, MVC force or EMG, jump height, take-off velocity, contact time, and jumping TTF. Independent of group, there was a threefold increase in blood lactate (p < 0.01) from pre-warm-up to post-fatigue and a significant decrease in MVC force (p = 0.048, Delta 8.1%) from post-warm-up to postfatigue. Results suggest that ankle CG increased and maintained skin temperature during recovery, decreased twitch half-relaxation times, and reduced GRF from a 50-cm drop height. However, ankle CG did not improve other performance measures, aid in recovery, or affect blood lactate clearance.